Variant Typesof Domination in Spinner Graph - N, Al-Harere M; Breesam, Athraa T (Al-Nahrain Journal of Science, 2019)
A new graph, finite, simple, undirected and connected, is introduced named spinner graph, and denoted by . This paper includes a study of the domination number (domination, independent domination, total domination, connected domination, restrained domination and, bi-domination) in spinner graph.